Avaliação dos fatores de risco intrínsecos de quedas em idosos institucionalizados - Dias, Roberta Bolzani de Miranda (2011)
This work had as a goal to evaluate the particular risk elements related to the elderly institutionalized in the city of Passo Fundo-RS. The study was characterized as being transverse of descriptive type. The population was composed of 40 elderly, being 27 women and 13 men, from seven Institutions of Long Staying for Elderly People (LPIs) of the city. The inclusion criteria were: to be 60 years old or more; to walk, even if with the device which helps to help and/or a help coming from outsiders. The exclusion criteria were the following: to present cognitive deficit which makes impossible the comprehension/imitation of verbal and/or simple motor activities; to stay in bed (to be restricted to stay in bed) or to be a wheelchair user; to present visual deficit and/or auditive strongly restricted and not compensated by use of glasses or a resonant amplification device. There were used as instruments of database: A questionnaire structured with socio-demographic and clinic data; Mini Mental State Exam (MMSE) Katz Index; Geriatric Depression Scale (GDS); Timed Up and Go (TUG) and the Berg Balance Scale (BBS). The data were analized by the descriptive statistics. To compare the frequencies of the qualitative variables it was used the likelihood ratio statistics. The Spearman Rank Correlation Coefficient was calculated to measure the association degree of the Time Up and Go Test variable with other quantitative variables. The comparisons of the quantitative variable average in study were accomplished over the Kruskall-Wallis test where there were a significant difference, it was accomplished the Student-Newman-Keuls test to identify where those differences occurred. The considered significance level was 5%. The elderly demonstrated an age average of 78,8 years old and the average time of institutionalization of 35,7 months. The most prevalent diseases were the systemic arterial hypertension (75,5%), and the depression (55%) and the cardiopathies (50%). The prevalence of the falls was of 62,5% and the average of suffered falls was 0,9, once that the men fell more than the women. From the 40 participants, (85%) showed cognitive deficit; regarding to the functional ability, (27,5%) were independent for all the activities; (50%) of the elderly had light depression, 14 (35%) had serious depression and 6 (15%) did not have depression; from TUG it was possible to evaluate the participants fall risk, whereby, (45%) had a low risk, (22,5%) showed a moderate risk and (32,5%) had a high risk. Regarding to the balance, (50%) showed deficit. The variables which demonstrated statistically significant difference related to the fall risk were: fall numbers (0,050); fall ratio (p = 0,004); march assistant device use (p=0,000); making use of tranquilizers (p = 0,031); BBS (0,000); KATZ (0,032). Finally, it is possible to say that the fall prevalence in institutionalized elderly is high and that is possible and also of a huge importance to evaluate the risk elements, because the intervention strategies will only be efficient when the elements are identified, minimized and eliminated